Serum neurofilament light chain levels in patients with cognitive deficits and movement disorders: comparison of cerebrospinal and serum neurofilament light chain levels with other biomarkers - Novobilský, Richard; Bartova, Petra; Lichá, Karin; Bar, Michal; Stejskal, David; Kusnierova, Pavlína (Frontiers in Human Neuroscience, 2023)
Background: Serum neurofilament light chain (NfL) is a non-specific marker of neuronal damage, including Alzheimer's disease (AD). We aimed to verify the reference interval (RI) of serum NfL using a highly sensitive ELISA, and to estimate the optimal cut-off value for neuronal damage. Our second objective was to compare NfL in cerebrospinal fluid (CSF) and serum (S) with the routine neurodegeneration biomarkers used in AD, and to assess their concentrations relative to the degree of cognitive deficit.Methods: Samples from 124 healthy volunteers were used to estimate the S NfL RI. For the comparison study, we used CSF and S samples from 112 patients with cognitive disorders.Cognitive functions were assessed using the Mini-Mental State Examination. ELISA assays were used to determine the CSF and S NfL levels, CSF -amyloid peptide42 (A42), CSF amyloid peptide40 (A40), CSF total tau protein (tTau), CSF phosphorylated tau protein (pTau) and CSF alpha-synuclein (S).The estimated RI of S NfL were 2.25-9.19 ng.L −1 . The cut-off value of S NfL for assessing the degree of neuronal impairment was 10.5 ng.L −1 . We found a moderate statistically significant correlation between S NfL and CSF A42 in the group with movement disorders, without dementia (rs=0.631; p=0.016); between S NfL and CSF A40 in the group with movement disorder plus dementia (rs=−0.750; p=0.052); between S NfL and CSF tTau in the control group (rs=0.689; p=0.009); and between S NfL and CSF pTau in the control group (rs=0.749; p=0.003). The nonparametric Kruskal-Wallis test revealed statistically significant differences between S NfL, CSF NfL, CSF A42, CSF tTau, and CSF pTau and diagnosis within groups. The highest kappa coefficients were found between the concentrations of S NfL and CSF NfL ( = 0.480) and between CSF NfL and CSF tTau (=0.351).Our results suggested that NfL and tTau in CSF could be replaced by the less-invasive determination of S NfL using a highly sensitive ELISA method. S NfL reflected the severity of cognitive deficits assessed by MMSE. However, S NfL is not specific to AD and does not appear to be a suitable biomarker for early diagnosis of AD.